Greener and Whiter Analytical Chemistry Using Cyrene as a More Sustainable and Eco-Friendlier Mobile Phase Constituent in Chromatography - Sami El Deeb; Khalid Abdelsamad; Maria Kristina Parr (Pharmaceuticals, 2023)
Cyrene (dihydrolevoglucosenone) was evaluated for the first time as a potential sustainable mobile phase solvent in reversed-phase chromatography. As a benign biodegradable solvent, Cyrene is an attractive replacement to classical non-green organic chromatographic solvents such as acetonitrile and a modifier, co-eluent to known green solvents such as ethanol. Compared to ethanol, Cyrene is less toxic, non-flammable, biobased, biodegradable, and a cheaper solvent. A fire safety spider chart was generated to compare the properties of Cyrene to ethanol and show its superiority as a greener solvent. Cyrene’s behavior, advantages, and drawbacks in reversed-phase chromatography, including the cut-off value of 350 nm, elution power, selectivity, and effect on the column, were investigated using a model drug mixture of moxifloxacin and metronidazole. A monolithic C18 (100 × 4.6 mm) column was used as a stationary phase. Different ratios of Cyrene: ethanol with an aqueous portion of sodium acetate buffer mobile phases were tested. A mobile phase consisting of Cyrene: ethanol: 0.1 M sodium acetate buffer pH 4.25 (8:13:79, v/v/v) was selected as the most suitable mobile phase system for separating and simultaneously determining metronidazole and moxifloxacin. The greenness and whiteness of the method were evaluated using the qualitative green assessment tool AGREE and the white analytical chemistry assessment tool RGB12. Further potentials of Cyrene as a solvent or modifier in normal phase chromatography, liquid chromatography–mass spectrometry, and supercritical fluid chromatography are discussed.